PENGARUH KARAKTERISTIK CEO, KOMISARIS INDEPENDEN DAN KUALITAS AUDIT TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Hendri Mauliansyah; Budi Safatul Anam; Zulkifli Umar (BE-HISZ : Journal of Economics and Accounting, 2024)
The purpose of this study was to examine the effect of CEO Characteristics, Independent Commissioners, and Audit Quality on Tax Avoidance in Automotive and Component companies listed on the Indonesia Stock Exchange. This type of research is a quantitative method. The population in this study were 60 samples of Automotive and Component companies listed on the Indonesia Stock Exchange. The object of this research is the Automotive and Component companies listed on the Indonesia Stock Exchange. Data analysis techniques in this study using multiple linear regression analysis. The type of data used in this study is secondary data. The results showed that CEO Characteristics, Independent Commissioners and Audit Quality had a positive effect on Tax Avoidance in Automotive and Component companies listed on the Indonesia Stock Exchange both simultaneously and partially